Support provision to schools in a context of HIV/AIDS, poverty and gender - Olsen, Sissel Tove. (University of the Western Cape, 2013)
Philosophiae Doctor - PhD === The school environment presents a valuable opportunity for the identification, monitoring and support of children made vulnerable by HIV/AIDS and poverty. Many children are caring for parents suffering from AIDS related illnesses and/or they are the main breadwimnner of the household. As a reult of HIV/AIDS and poverty therefore, children might be dropping out of school, or their ability to performadequately at school might be significantly reduced. The main aim of this study was to use a case study approach to explore and describe support provision in a South African formal school, examining in particular, the relative significance of leadership, organisational development and gender-related matters in addressing the needs of children made vulnerableby HIV/AIDS and poverty.The availability and quality of this support is analysed within the context of the Western Cape Education Department (WECD) transforming itself from a system focussed on controlling schools to a system focused on supporting schools. === South Africa